Le faus françeis d’Angleterre en tant que langue seconde ? Quelques phénomènes syntaxiques indicatifs - Yela Schauwecker (Revue des Langues Romanes)
In this article I question the characterization of the faus franceis d’Angleterre as a dialect of Medieval French. I do so first of all on grounds of the fact that Anglo-French (AF) was spoken by an extremely heterogeneous group of speakers coming from very different social and linguistic backgrounds. Therefore, one should not use linguistic factors observed in a given author’s text to draw conclusions regarding AF as a whole. While it is generally accepted that the majority of speakers of AF were bilingual, the scenario of bilingualism from birth only applies to a comparatively small portion of the population. I will show that roughly one half of the texts show features suggesting that the author has an L2 French background. As a consequence, the observed phenomena should not be considered dialectal features of AF as a whole, or as language change characterizing AF in general, but rather as idiolectal features in a given author’s L2. Technically, my argument rests on the distribution of several verb-related (morpho)syntactic phenomena, which set AF apart from continental Old French (OF), namely auxiliary selection, use of the pronoun eux, motion-event descriptions and directed motion constructions. My study is corpus-based and utilizes data from the ANHdb (Anglo-Norman Hub database, cf. Schauwecker and Stein 2016) as well as the BFM (Base de français Médiéval, 2016).